2013
DOI: 10.1103/physrevb.88.201302
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of spin-orbit splitting and phonon-assisted optical transitions in the valence band by internal photoemission spectroscopy

Abstract: We employ internal photoemission spectroscopy to directly measure the valence-band Van Hove singularity, and identify phonons participating in indirect intervalence-band optical transitions. Photoemission of holes photoexcited through transitions between valence bands displays a clear and resolvable threshold, unlike previous reports of interband critical points which become obscure in doped materials. We also demonstrate the enhancement of optical phonon-assisted features primarily contributing to the photoem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…26,27 It was shown that the carrier-phonon coupling plays an important role in the intervalence-band transitions. 28 Photoexcited holes in the light-hole band or spin-orbit split-off band initially relax, mainly through the emission of optical phonons, typically within a sub-picosecond timescale. The subsequent relaxation proceeds through the dominant hole-hole scattering mechanism, which causes a redistribution of energies among the hot and cold holes.…”
Section: Hot-cold Carrier Interactionsmentioning
confidence: 99%
“…26,27 It was shown that the carrier-phonon coupling plays an important role in the intervalence-band transitions. 28 Photoexcited holes in the light-hole band or spin-orbit split-off band initially relax, mainly through the emission of optical phonons, typically within a sub-picosecond timescale. The subsequent relaxation proceeds through the dominant hole-hole scattering mechanism, which causes a redistribution of energies among the hot and cold holes.…”
Section: Hot-cold Carrier Interactionsmentioning
confidence: 99%
“…2A , where it can be seen that the peak responsivity is 7.3 A/W, which is about five orders of magnitude higher than that of the OPHED; for the responsivity calibration method, see the Supplementary Materials. The near-IR (NIR; 80 to 300 THz) photoresponse mechanism is caused by the SO band absorption (SOA) and consists of three main steps: (i) photoabsorption that excites the holes from the highly doped emitters (i.e., injector and absorber), where a direct transition occurs from light or heavy hole band to the SO band; (ii) scattering-assisted escape of the photoexcited carriers; and (iii) collection of the escaped carriers ( 35 , 36 ). The response mechanism of the mid-IR (MIR) and far-IR (FIR) photons (16 to 80 THz) is primarily caused by the free carrier absorption (FCA)–based internal photoemission.…”
Section: Resultsmentioning
confidence: 99%
“…4C , under the zero bias, the IR photons stochastically changed the momentum and energy of the holes in both the injector and the absorber. The occurred absorption includes the FCA and SOA ( 35 , 36 ). Then, the asymmetry of the repeated unit of the barrier potential biased the holes’ motion to the left due to the asymmetric relaxation ( 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%